Exploration of cobalt@N-doped carbon nanocomposites toward hydrogen peroxide (H2O2) electrosynthesis: A two level investigation through the RRDE analysis and a polymer-based electrolyzer implementation. (20th December 2020) - Ferrara, Marcello; Bevilacqua, Manuela; Melchionna, Michele; Criado, Alejandro; Crosera, Matteo; Tavagnacco, Claudio; Vizza, Francesco; Fornasiero, Paolo
Highlights: Cobalt–carbon core shells were established to be highly selective for 2 e − ORR pathway. Co encapsulated N-carbon was used as electrocatalyst for the selective H2 O2 formation. Rotating Ring Disk Electrode was used to rationalize structure/activity relationship. The electrode implementation in a PEM static flow electrolyzer setup was investigated. Abstract: The Oxygen Reduction Reaction (ORR) catalyzed by N-carbon electrocatalyst was investigated, focusing on the fundamental features for the selective H2 O2 formation. The electrochemical characterization was primarily performed by the use of the Rotating Ring Disk Electrode (RRDE) tool in both hydrodynamic Linear Sweep Voltammetry (LSV) mode and by Chronoamperometry (CA) measurement. We rationalized the structure/activity relationship, reaching a new state-of-the-art in terms of current density for the H2 O2 generation. The study also explored the performance in relation with the electrode deposit procedure that is of fundamental importance to achieve a suitable macroscopic electrode preparation. Furthermore, the electrode implementation in a polymer membrane static flow electrolyzer setup, was evaluated to understand how the material catalytic features such as current ranges and selectivity scale up from a classical three electrode system to a more realistic application-focused environment.